The promise of behavioral economics for understanding decision‐making in the court - Wilson, Theodore (Criminology & public policy, 2019)
Decision‐making scholars often limit their purview to the decision to offend, whereas sentencing scholars focus on court case processing within administrative data sets. What is missing between these two camps is an incorporation of the sanctioning process into offender decision‐making and an integration of relevant findings from offender decision‐making and behavioral economics into courtroom actor decision‐making. In this article, I highlight several specific concepts from behavioral economics that can be applied to the court and interpret existing sentencing research in light of these same behavioral economic concepts.